The Co-N-C Catalyst Synthesized With a Hard-Template and Etching Method to Achieve Well-Dispersed Active Sites for Ethylbenzene Oxidation - Shen, Chun; Jie, Shanshan; Chen, Hong; Liu, Zhigang (Frontiers in Chemistry, 2019)
Biomass obtained from organic residues gradually becomes one of the optimal renewable feedstock of value added chemicals. Herein, the Co-N-C catalyst was prepared via a hard-template and etching method using the casein as C and N sources, magnesium oxide as the template and cobalt porphyrin as the metal precursor. The obtained Co-N-C catalyst exhibited excellent catalytic performance for selective oxidation of ethylbenzene with a conversion rate of 96.5% under mild conditions. Moreover, the catalysts were investigated by techniques such as BET, XRD, Raman, TEM and XPS. The results showed that the etching progress could improve the dispersion of Co and the exposure of active sites. Herein, the efficient oxidation of ethylbenzene was attributed to the well-dispersed Co-N species and the increased specific surface area.